Arbuscular mycorrhizal fungi symbiosis enhances growth, nutrient uptake, and oil quality in sunflower–pumpkin under intercropping systems - Alayafi, Aisha A. M.; Alharbi, Basmah M.; Abdulmajeed, Awatif M.; Alnusaire, Taghreed S.; ALrashidi, Ayshah Aysh; AL-Balawi, Siham M.; Khalaf Anazi, Hanan; Alghanem, Suliman M. S.; Al zoubi, Omar Mahmoud; Soliman, Mona H. (Frontiers in Plant Science, 2025)
IntroductionThis study evaluated the effects of Funneliformis mosseae, an arbuscular mycorrhizal (AM) fungus, on nutrient uptake, biomass production, and oil quality in sunflower (Helianthus annuus) and pumpkin (Cucurbita pepo) under both sole and intercropping field systems.MethodsA factorial experimental design was conducted over two growing seasons (2023 and 2024), involving three cropping systems: sunflower monoculture, pumpkin monoculture, and additive sunflower–pumpkin intercropping. Each system was assessed with and without AM inoculation to determine the interactive effects of mycorrhizal symbiosis and cropping pattern.ResultsAM inoculation significantly improved root colonization, especially in intercropped pumpkins, and enhanced key plant growth parameters, including chlorophyll content, plant height, leaf number, biomass, and reproductive traits. The highest performance was recorded in AM-treated intercropped systems for both crops. Seed weight increased notably under AM inoculation, reflecting improved reproductive development. Analysis of mineral nutrient content revealed substantial improvements in macro- and micronutrient uptake with AM symbiosis. Intercropped AM-treated plants showed enhanced levels of phosphorus, potassium, calcium, zinc, and iron compared to their non-mycorrhizal counterparts. Additionally, AM treatments led to a marked improvement in oil yield and quality. In particular, AM-inoculated sunflower and pumpkin seeds exhibited higher total oil content and a favorable shift in fatty acid composition, characterized by increased oleic acid and reduced linoleic acid concentrations.DiscussionThese findings highlight the synergistic potential of integrating AM fungal inoculation with intercropping practices to enhance crop productivity, nutrient use efficiency, and oilseed quality. The results support the adoption of AM fungi as a sustainable biofertilizer strategy in modern agroecosystems.